(untitled) (International Journal of Applied Research in Management and Economics, 2020)
In the specialized literature there is no unitary opinion regarding the definition of efficient management and managerial performance. For the managers of the Romanian organization, subject to multiple and increasingly complex contextual and endogenous challenges and prone to informational "claustrophobia" due to the volume of information that must be decisively capitalized, the effectiveness of their performance is much more important. A first factor that influences the level of managerial performance is the competence of those who exercise the management processes, respectively of the managers, but also of those who operationalize the decisions, i.e., of the subordinates. The managerial activity carried out by the principals and deputy principals of the pre-university education units is evaluated following certain components and attributions from the job description according to some performance criteria. The research aimed to analyze the performance criteria and the influence of the manager on the performance criteria in the case of management staff in a school organization. The most important criterion is the design of the coordination strategy and directions for the development of the educational unit, and the least important is the monitoring / evaluation / control of the activities in the educational unit. The conclusion of contracts with economic agents, NGOs and other organizations regarding the development of projects was evaluated negatively by the majority of respondents, as it has no influence on the increase of performance. The management of the school must play a catalytic role among teachers, in the sense of promoting, identifying, stimulating and rewarding creative teachers who participate in forming a positive image and increasing the prestige of the school in the community by creating its own organizational culture.